Information Fiqh As The Foundation Of Islamic Communication In Handling Hoaxes In The Digital Era - Fauzi, Fauzi; Marhamah, Marhamah (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2025)
This study aims to describe adolescents' understanding of information and optimization and optimization of information fiqh as the basis for Islamic communication in the digital era. This study uses a combination method (mixed methods) by combining quantitative and qualitative data. Quantitative data were collected through the distribution of online questionnaires to 102 adolescents in Lhokseumawe City. Quantitative data were analyzed using univariate analysis. While qualitative data collection was carried out by interviewing 3 informants who were used to explain quantitative data. Qualitative data were analyzed using the Miles and Huberman model analysis. The results of the study describe adolescents' understanding of hoax information as being in the very good category. However, understanding of information fiqh as the basis for Islamic communication is still low. The results of interviews with fiqh scholars explain that information fiqh has not been clearly formulated and disseminated to the public as a guideline in producing and disseminating information. In fact, information fiqh is a solution to respond to increasingly widespread hoax information in the digital era.